2001
DOI: 10.1093/gerona/56.suppl_2.65
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake, Dietary Patterns, and Changes With Age: An Epidemiological Perspective

Abstract: Cohort and cross-sectional data were reviewed to describe the changes in dietary intake with age. Total energy intake decreases varied substantially with age, by 1000 to 1200 kcal in men and by 600 to 800 kcal in women. This resulted in concomitant declines in most nutrient intakes. For some nutrients, substantial numbers of older Americans consumed only one fifth to one third of the recommended dietary allowance. For most nutrients, research is lacking with which to judge the health impact of reduced nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
176
1
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(201 citation statements)
references
References 32 publications
10
176
1
6
Order By: Relevance
“…Therefore, it is of particular interest for the elderly that even the Mediterranean diet pattern at low-energy levels fails to meet all nutrient requirements (Padro et al, 2002). The decrease of energy consumption observed with increasing age (Moreiras-Varela et al, 1996;Alberti-Fidanza et al, 1999;Wakimoto & Block, 2001) could therefore be considered as one of the most essential factors for inadequate nutrient intake in the elderly. In the present study, we observed a general trend concerning the relation between nutrient intake and energy consumption that concurs with previously published data (Willett, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is of particular interest for the elderly that even the Mediterranean diet pattern at low-energy levels fails to meet all nutrient requirements (Padro et al, 2002). The decrease of energy consumption observed with increasing age (Moreiras-Varela et al, 1996;Alberti-Fidanza et al, 1999;Wakimoto & Block, 2001) could therefore be considered as one of the most essential factors for inadequate nutrient intake in the elderly. In the present study, we observed a general trend concerning the relation between nutrient intake and energy consumption that concurs with previously published data (Willett, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…However, meeting nutrient intake recommendations is difficult at lowenergy consumption level, even in the case of a diet based on the Mediterranean diet pattern (Padro et al, 2002). A decline in energy consumption directly related to increasing age has been observed, which may result in noncompliance of the age-specific nutrient requirements (Moreiras-Varela et al, 1996;Alberti-Fidanza et al, 1999;Wakimoto & Block, 2001). Nutritional deficiencies are more frequent in old people than in other age groups, and their effects are much more serious (Suboticanec et al, 1989;Chandra et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…With advancing age, there is a decline in energy consumption (Wakimoto and Block 2001;de Boer et al 2013), and depending on energy expenditure and on energy balance, older people may lose weight. It seems that there are two general mechanisms involved in the development of the age-related decline in appetite: (1) reduced drive to eat (hunger) resulting from lower energy requirements, and (2) more rapidly acting or more potent inhibitory satiety signals.…”
Section: General Mechanisms Of the Anorexia Of Agingmentioning
confidence: 99%
“…Diversos estudios nacionales 19,30,31 , regionales 13,15 , otros países en vías de desarrollo 27 e incluso de países desarrollados 26,28,32,33 han mostrado una ingesta inadecuada de zinc en los adultos mayores, acentuándose la reducción de la ingesta con la edad 5 . Por otra parte, una ingesta insufi ciente de cobre en este grupo etario ha sido demostrada en estudios nacionales 19,29 y algunos realizados en países desarrollados 32,34 .…”
Section: Prevalencia De Deficiencia De Zn Y Cu En Adultos Mayores -Munclassified
“…El aumento de las expectativas de vida es un fenómeno creciente a nivel mundial que ha llevado a un aumento progresivo del número de adultos mayores. Este grupo etario es más vulnerable a experimentar defi ciencias de micronutrientes debido a un menor consumo de alimentos por limitaciones socioeconómicas, aislamiento social, menor actividad física o por una anorexia originada por alteraciones sensoriales, consumo de algunos medicamentos o a factores psicológicos 5,6 . A esto se agregan difi cultades en la digestión por problemas en la masticación por la pérdida de piezas dentales y en la absorción de algunos nutrientes a consecuencias de posibles alteraciones en la función gastrointestinal 7,8 .…”
unclassified